Lactation performance of Red Chittagong Cattle and effects of environmental factors (Bangladesh Veterinarian, 2010)
The present study was undertaken to estimate effects of environmental factors onmilk production traits in Red Chittagong Cattle (RCC). A total of 103 milk yield recordsof 45 RCC cows obtained between 2005 and 2009 were analysed. Actual lactation yield,lactation length, daily milk yield and dry period were estimated as 500.7 ± 19.3 kg, 259.6 ±6.2 days, 1.9 ± 0.1 kg and 162.4 ± 7.7 days, respectively. Age and season correctedlactation yield, 305 day milk yield and daily milk yield were estimated as 605.4 ± 22.9,677.1 ± 19.4 and 2.2 ± 0.1 kg, respectively. Sex of calf and season of birth did notsignificantly (P>0.05) affect production, but lactation order significantly (P0.05) on the traitsanalysed except daily milk yield (P